2007
DOI: 10.1159/000110787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase and Nitric Oxide Synthase Inhibitors on Streptozotocin-Induced Hyperalgesia in Rats

Abstract: We examined a possible involvement of cyclooxygenase (COX) and nitric oxide synthase (NOS) products in hyperalgesia occurring during streptozotocin (STZ)-induced diabetes. Indomethacin and celecoxib were used as relatively selective inhibitors of COX-1 and COX-2, respectively. NOS inhibitors included: non-specific inhibitor NG-nitro-L-arginine and L-N6-(1-iminoethyl)lysine preferentially acting on inducible NOS (iNOS) as well as 7-nitroindazole relatively specific inhibitor neuronal NOS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
6
22
1
Order By: Relevance
“…The same authors observed that co-administration of two NSAIDs (indomethacin and celecoxib) also prevent this mechanical hyperalgesia. 70 These kind of results had already been observed with two other NSAIDs (ibuprofen and rofecoxib), 71 whereas NSAIDs did not showed analgesic effects. At last, IL-6, known to be implicated both in the neural degeneration and the regeneration process, displayed in the rat as a preventive effect on heat hypoalgesia.…”
Section: Preventive Strategiesmentioning
confidence: 69%
“…The same authors observed that co-administration of two NSAIDs (indomethacin and celecoxib) also prevent this mechanical hyperalgesia. 70 These kind of results had already been observed with two other NSAIDs (ibuprofen and rofecoxib), 71 whereas NSAIDs did not showed analgesic effects. At last, IL-6, known to be implicated both in the neural degeneration and the regeneration process, displayed in the rat as a preventive effect on heat hypoalgesia.…”
Section: Preventive Strategiesmentioning
confidence: 69%
“…In vincristine-induced neuropathy, the reported effects of NO and nitric oxide synthase (NOS) on the pain are conflicting. Kamei et al (36) reported that vincristine administration decreased the levels of NO metabolites, cGMP and protein levels of neuronal NOS in the spinal cord, and a NOS inhibitor reversed the analgesic effect of a NOS substrate, while Bujalska and Gumułka reported that NOS inhibitors prevented the development of hyperalgesia induced by vincristine administration (37). In an inflammatory cellular model, Melilotus extract decreased the secretion of NO and expression of inducible NOS in a dose-dependent manner (38).…”
Section: Discussionmentioning
confidence: 99%
“…So, the noted rise in serum nitrite levels in the present investigation suggests the enhanced expression of eNOS. Moreover, it has been documented that increase in nNOS is not responsible for diabetic neuropathy pain, 29) while its decreased expression may do so. 30) Further, it has also been noticed that net nitric oxide concentration is reduced during diabetes.…”
Section: Discussionmentioning
confidence: 99%